Review articleImmune regulation and viral diversity as correlates of natural and treatment induced immune control in persistent hepatitis B virus (HBV) infection - Parfieniuk-Kowerda, Anna; Jaroszewicz, Jerzy; Flisiak, Robert (Clinical and Experimental Hepatology, 2015)
In long-lasting chronic hepatitis B, the phenomenon of cytotoxic CD8 T lymphocytes (CTL) exhaustion and unresponsiveness to HBV-specific stimuli was shown to be crucial for the loss of immune control of the virus and disease activity. There is evidence that Tregs, Th17 cells and Bregs seem to be important in pathogenesis of the immunological dysfunction and loss of HBV-specific activity of cytotoxic CD8 T-cells. Th17-driven immune response was shown to be important in pathogenesis of acute HBV infection and exacerbated chronic hepatitis B along with Th1 response contributing to hepatocellular damage due to proinflammatory activities of Th17-derived cytokines, mainly IL-17A. Treg cell responses may be either beneficial or harmful in HBV infection by limiting liver immunopathology or suppressing protective T cell responses, thus promoting virus replication and survival. Thus, Treg/Th17 equilibrium seems to be crucial for the outcomes of HBV infection.